Bacteriological Profile and Antibiotic Susceptibility Patterns of Wound Infections at a Public Tertiary Hospital in Sana'a Governorate, Yemen - Gamil T. Abdul Mughni; Butheina A. Alamrani; Arwa M. Othman; Sadeq S. Abdulmogni; Naif M. Al-Haidary; Ahmed Y. M. Aljamrah (University of Science and Technology, Sana’a, Yemen, 2025)
Background: Wound infections are a leading cause of morbidity and mortality globally, representing one of the most prevalent nosocomial infections. The etiological agents vary by geographic region, and there is a growing incidence of antibiotic resistance among these pathogens. This study retrospectively analyzed the bacterial species isolated from patients with wound infections and their antibiotic susceptibility patterns at a public tertiary hospital in Sana'a Governorate, Yemen. Methods: A retrospective cross-sectional study was conducted to identify the bacterial species causing wound infections and their antibiotic susceptibility patterns among patients admitted to the 48 Model Hospital in Sana’a Governorate from January 2020 to December 2020. This study included all patients diagnosed with wound infections and undergoing culture and antibiotic susceptibility testing during the study period. Results: Of the 386 patients with wound swab cultures, 290 (75.1%) had infections caused by a single bacterial species, most frequently among males (98.6%). Among the isolates, Gram-negative bacilli accounted for 61.4%, while Gram-positive cocci comprised 38.6%. Staphylococcus aureus was the most frequently isolated bacterial species (38.3%), followed by Pseudomonas aeruginosa (36.6%) and Klebsiella spp. (11.7%). Vancomycin showed the highest efficacy against Gram-positive isolates (100% sensitivity), followed by moxifloxacin (90.9%), linezolid (86.2%), and methicillin (68.5%), whereas amoxicillin/clavulanic acid and amoxicillin showed the lowest activity. Among Gram-negative isolates, imipenem demonstrated the highest activity (90.4%), followed by ceftriaxone/tazobactam (80.2%), amikacin (78.1%), and gentamicin (77.1%). However, cefotaxime, ceftazidime, and cefuroxime showed limited efficacy. For P. aeruginosa, imipenem remained the most effective agent (90.5%), followed by amikacin (78.6%) and tazobactam/piperacillin (70%). Conclusion: Wound infections are predominantly caused by Gram-negative bacilli, particularly P. aeruginosa and Klebsiella spp., with S. aureus being the most common Gram-positive isolate. The majority of infections occur among male patients. While high levels of resistance to commonly used antibiotics are observed, vancomycin remains fully effective against Gram-positive isolates, and imipenem demonstrates the highest efficacy against Gram-negative bacteria, including P. aeruginosa. The high level of antibiotic resistance of bacterial species isolated from wound infections emphasizes the need for evidence-based empirical treatment guided by local susceptibility patterns.